Recycling a railcar classic - Borland, James (Nickel Development Institute, 1988)
This case study describes the quality and longevity of stainless steel railcars of Canada's transcontinental passenger fleet.
"Reprinted from: Nickel, Volume 10, number 4, June 1995."
Keywords: Railroad cars -- Materials -- Recycling.; elektronické knihy; electronic books